Factors Related to Self-reliance and Technology Acceptance among the Elderly Digital Age in Nong Khai Province - Phatanet, Paijit (NEU ACADEMIC AND RESEARCH JOURNAL, 2024)
This research is a quantitative study with the following objectives: 1) To study the level of self-reliance among the elderly in Nong Khai Province. 2) To study the level of technology acceptance among the elderly in Nong Khai Province. 3) To compare the differences in personal factors with the technology acceptance of the elderly in Nong Khai Province. 4) To study the relationship between self-reliance and technology acceptance of the elderly in Nong Khai Province. The study uses a sample of 398 elderly individuals in Nong Khai Province through questionnaires. The statistics used in the study include frequency, percentage, mean, standard deviation, T-test hypothesis testing, one-way ANOVA or F-test, and Pearson’s Correlation Coefficient. The study found that: 1) The self-reliance of the elderly is highest in the physical aspect, followed by social, psychological, and financial aspects, respectively. 2) The technology acceptance of the elderly is highest in perceived benefits, followed by behavioral intention to use, perceived enjoyment, social influence, and perceived ease of use, respectively. 3) Elderly individuals with different ages, education levels, occupations, and incomes have significantly different technology acceptance at the 0.05 level. 4) It cannot be concluded that the self-reliance of the elderly is related to the technology acceptance of the elderly at the 0.01 significance level. The findings from this study will provide valuable in designing policies to improve the quality of life, economy, and society of the elderly in Nong Khai Province.